CooC11 and CooC7: the development and validation of age appropriate children's perceived cooking competence measures - Moira Dean; Johann Issartel; Tony Benson; Amanda McCloat; Elaine Mooney; Claire McKernan; Laura Dunne; Sarah F. Brennan; Sarah E. Moore; Danielle McCarthy; Jayne V. Woodside; Fiona Lavelle (BMC, 2021)
Abstract Background Learning cooking skills during childhood and adolescence is associated with positive dietary outcomes in adulthood as well as being tracked from adolescence to adulthood. In addition studies have found that perceived competence to be a greater motivator to perform a behaviour than actual competence. However, a lack of validated tools that effectively measure behavioural and dietary changes including cooking confidence in children is a limitation. Therefore, this research aimed to develop and validate age-appropriate perceived cooking competence measures for younger and older primary school aged children. Methods Two measures of perceived Cooking Competence (CooC11 and CooC7) for older (8-12 years) and younger (6-7 years) children were developed from a critical evaluation of publically available recommendations and expert consultation. The cooking skills within the measures were illustrated by a graphic designer in consultation with a chef and reviewed in an iterative manner by the research team. The measures were piloted for clarity, ease of use and initial face validity. Multiple studies were used for both CooC11 and CooC7 to establish psychometric properties of the measures, temporal stability, internal consistency reliability, construct validity, as well as responsiveness to change for CooC11. Analysis included Exploratory Factor Analysis, Confirmatory Factor Analysis, Intraclass Correlation Coefficients, Pearson's Correlations, ANOVAs and Cronbach's Alphas. Results Both measures had high levels of face validity and received positive user feedback. Two factors were shown in both measures with the measures showing excellent temporal stability (ICC > 0.9) and good internal consistency (Cronbach's Alphas > 0.7). Both measures showed initial discriminant validity, with significant differences (P< 0.001) between those who reported assisting their parents with dinner preparation and those who did not. Additionally, CooC11 was significantly correlated with an adult cooking measure and had a significant responsiveness to change (P< 0.01). Conclusions The CooC11 and CooC7 are the first validated age-appropriate measures for assessing children's perceived Cooking Competence for ages 8-12 and 6-7 years respectively. They can be used to evaluate the efficacy of children's cooking intervention studies or school nutrition education programmes.